Optimization of a small molecule inhibitor of secondary nucleation in α-synuclein aggregation - Staats, Roxine; Brotzakis, Z. Faidon; Chia, Sean; Horne, Robert I.; Vendruscolo, Michele (Frontiers in Molecular Biosciences, 2023)
Parkinson’s disease is characterised by the deposition in the brain of amyloid aggregates of α-synuclein. The surfaces of these amyloid aggregates can catalyse the formation of new aggregates, giving rise to a positive feedback mechanism responsible for the rapid proliferation of α-synuclein deposits. We report a procedure to enhance the potency of a small molecule to inhibit the aggregate proliferation process using a combination of in silico and in vitro methods. The optimized small molecule shows potency already at a compound:protein stoichiometry of 1:20. These results illustrate a strategy to accelerate the optimisation of small molecules against α-synuclein aggregation by targeting secondary nucleation.